Advances of nanoparticle-mediated diagnostic and theranostic strategies for atherosclerosis - Lin, Lin; Chen, Lin; Yan, Juan; Chen, Peirong; Du, Jiahui; Zhu, Junpeng; Yang, Xinyu; Geng, Boxin; Li, Lang; Zeng, Wen (Frontiers in Bioengineering and Biotechnology, 2023)
Atherosclerotic plaque remains the primary cause of morbidity and mortality worldwide. Accurate assessment of the degree of atherosclerotic plaque is critical for predicting the risk of atherosclerotic plaque and monitoring the results after intervention. Compared with traditional technology, the imaging technologies of nanoparticles have distinct advantages and great development prospects in the identification and characterization of vulnerable atherosclerotic plaque. Here, we systematically summarize the latest advances of targeted nanoparticle approaches in the diagnosis of atherosclerotic plaque, including multimodal imaging, fluorescence imaging, photoacoustic imaging, exosome diagnosis, and highlighted the theranostic progress as a new therapeutic strategy. Finally, we discuss the major challenges that need to be addressed for future development and clinical transformation.